HOW BRAND IMAGE AND TECHNOLOGY ACCEPTANCE SHAPE CUSTOMER SATISFACTION: EVIDENCE FROM BLU BY BCA DIGITAL (POLITEKNIK LP3I JAKARTA, 2026)
As competition in the digital banking industry continues to intensify, understanding the factors that influence customer satisfaction has become increasingly important for sustaining competitive advantage. This study aims to examine the effects of Brand Image, Perceived Usefulness, and Perceived Ease of Use on Customer Satisfaction among users of blu by BCA Digital in Indonesia. Data were collected through an online survey, yielding 389 valid responses from active blu by BCA Digital users selected using purposive sampling. Multiple linear regression analysis was employed to test the proposed hypotheses. The results indicate that Brand Image, Perceived Usefulness, and Perceived Ease of Use each have a positive and significant effect on Customer Satisfaction, with Brand Image demonstrating the strongest influence. Furthermore, the three variables jointly explain 39.1% of the variance in customer satisfaction. These findings contribute to the digital banking literature by highlighting the complementary roles of branding and technology acceptance in shaping customer satisfaction. The results also provide managerial insights for digital banking providers to strengthen brand reputation while continuously improving application functionality and usability to enhance customer satisfaction and long-term competitiveness.